Interactive effects of salinity, temperature and food web configuration on performance and harmfulness of the raphidophyte Heterosigma akashiwo - Giesler, Jakob Karl; Lemley, Daniel Alan; Adams, Janine Barbara; Moorthi, Stefanie Devi (Frontiers in Marine Science, 2023)
The cosmopolitan raphidophyte Heterosigma akashiwo commonly forms harmful algal blooms (HABs) in diverse estuaries discharging into Algoa Bay, South Africa, potentially leading to hypoxia, fish kills and a decline in key primary consumers. Despite the high environmental variability in these estuaries, little is known about how abiotic factors such as temperature and salinity constrain bloom formation and harmfulness of H. akashiwo. The present study therefore investigates growth, competition, and grazing interactions of H. akashiwo in laboratory experiments in response to two naturally relevant levels of salinity (15, 30) and temperature (16, 22°C), respectively. Experiments were set up with the naturally co-occurring dinoflagellate competitor Heterocapsa rotundata and two estuarine microzooplankton consumers, i.e., nauplii of the copepod Acartia tonsa and the rotifer Brachionus plicatilis. In monoculture, H. akashiwo growth was promoted at high temperature – low salinity conditions, while H. rotundata thrived under low temperature – high salinity conditions. In polyculture, H. akashiwo dominated at high temperature irrespective of the salinity regime, while at low temperature, it only dominated at low salinity and was suppressed by H. rotundata at high salinity. Grazing assays revealed highly negative effects of H. akashiwo on copepod nauplii survival and growth as well as mucus-induced immobilization, especially at high temperatures in combination with low salinity, while the estuarine adapted rotifers showed highest mortalities at the higher salinity level. The presence of H. rotundata significantly alleviated the harmful effects of H. akashiwo on both grazers, and the selectively feeding copepod nauplii actively avoided H. akashiwo when non-harmful prey was present. Overall, this study demonstrates that population dynamics and harmful effects of H. akashiwo are interactively determined by both abiotic conditions and food web configuration, implying competitor and consumer specific tolerances to the abiotic environment and their susceptibility to the harmful alga H. akashiwo.